Agglomeration with the pros and cons of labor heterogeneity - Ryusuke Ihara (European Regional Science Association (ERSA), 2011)
Using a simple two-region model with the positive and negative effects of labor heterogeneity, we investigate the agglomeration pattern of entrepreneurs and the commuting pattern of heterogeneous workers. Labor heterogeneity is a source of productivity for e.g. high-tech industries as well as is an obstacle to e.g. mass production. As a result, we show that entrepreneurs tend to concentrate to a region hence regional labor markets are united with interregional commuting when (i) the commuting cost or (ii) the adjustment cost of labor heterogeneity is low, and when (iii) the input of heterogeneous labor is large. These results explain: the progress of urbanization with the decrease in commuting costs; the difference in the agglomeration tendency of industries.
Keywords: 330